Consumer stockpiling and sales promotions - Anna Lu (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
In retailing markets of storable goods, consumer behavior is typically characterized by stockpiling. While existing research has developed rich models for such strategic consumer behavior, little is known about how sellers should ideally respond to it. In this paper, we provide insights into how frequency and depth of promotions affect consumer purchases and seller revenues in the long run. We show an application to the U.S. market for laundry detergent. We use estimates from a structural dynamic demand model to simulate different pricing policies and find that in the detergent market, an increase in promotion depth is more effective than a change in promotion length. Our results suggest that this finding can be translated to markets with a large heterogeneity in storage costs and steady consumption rates.
Keywords: M31; D22; L11; 330; Promotion; Frequency; Depth; Stockpiling; Storable Goods